Development of Language Learning Evaluation E-Module Using K-Vsoft Flipbook Maker Application - Yanti Arasi Sidabutar; Leonita Maria Efipanias Manihuruk; Dyan Wulan Sari Hs; Marlina Agkris Tambunan (CV Putra Publisher, 2026)
In the modern era or the era of the development of Science and Technology (IPTEK), technology has become a common thing, the teaching and learning process can be done with the help of various learning media related to Information Technology (IT), for example the use of hardware or software that can increase effectiveness and support the learning process. With the advancement of technology like this, teachers in delivering learning to their students are not optimal if they only lecture. It would be better if teachers were able to package learning information in an interesting form. Delivering interesting information will help increase students' interest in learning. Therefore, education can lead to the use of technology, one of which is by using technology-based learning media. The selection and use of the right learning media will certainly help students achieve learning goals. Therefore, in this study the author developed teaching materials in the form of e-modules containing using the kvisoft flipbook maker application. E-modules are developed in accordance with the format for writing good e-modules, namely paying attention to: learning objectives, materials, case examples, case assignments, exercises, summaries, and reflections. E-modules are made interesting and interactive and contain learning videos so that students better understand the material being studied. This study uses a research and development (R&D) method adapted from the 4-D model (four D; Define, Design, development, Disseminate). The target of this development research is to produce a product in the form of an e-module that can be accessed via smartphone and laptop/computer. In addition to producing IPR from the e-module product, the author also targets the output in the form of a scientific publication in the accredited journal sinta 4.